2020
DOI: 10.1111/jftr.12398
|View full text |Cite
|
Sign up to set email alerts
|

How families matter for health inequality during the COVID‐19 pandemic

Abstract: We theorize that the social conditions surrounding the coronavirus disease 2019 (COVID‐19) pandemic have the potential to increase the importance of families for health and widen existing inequalities. We suggest three primary tenets important for understanding families and health during COVID‐19. First, risks of specific COVID‐19 outcomes and other health problems are unevenly distributed across families. Second, how families impact health during the COVID‐19 pandemic is conditional on public policies, organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Because of the cross-sectional nature of this observational study, causation can never be exactly known. It is possible that the racial and income differences observed in this study might be partially attributed to other social and political events and conflicts (e.g., police brutality, racism, Black Lives Matter Movement) that were simultaneously occurring in the U.S. in the era of the COVID-19 pandemic (Thomeer et al, 2020). More research is needed to understand the complexity of the dynamic interplay of social, political, and economic factors in families' lives during a pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the cross-sectional nature of this observational study, causation can never be exactly known. It is possible that the racial and income differences observed in this study might be partially attributed to other social and political events and conflicts (e.g., police brutality, racism, Black Lives Matter Movement) that were simultaneously occurring in the U.S. in the era of the COVID-19 pandemic (Thomeer et al, 2020). More research is needed to understand the complexity of the dynamic interplay of social, political, and economic factors in families' lives during a pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…As theorized by the stress process model [ 25 ], different levels of exposure to various stressors together with access to resources (e.g., financial, social) create a process of stress that in turn has deleterious consequences on well-being. The pandemic itself brought with it many stressors and reduced people’s resources, limiting availability of social support and inducing financial insecurity [ 2 , 26 ]. Following from the stress process model, we expect that the greater levels of stressors would contribute to worse mental health generally, as already well-documented [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the epidemic, children consume less fruit and vegetables and reach healthy meals less (Josephson et al, 2021;Patrick et al, 2020;Tar & Atik, 2021), and they face childhood obesity Pietrabissa et al, 2021;Couper-Kenney & Riddell, 2021), Type-1 diabetes in children has increased due to lifestyle changes (Brener et al, 2020), depending on the education and income level of the family. Moreover, they live in homes with irregular working environments (Thomeer, Yahirun, & Colón-López, 2020), crowded and inadequate home environments increase the risk of COVID-19 and infectious diseases in children (Freedson, 2021;Suleman et al, 2020). Westrupp et al (2021), in the research of low-income families; It was found that while working from home, they had difficulties in providing care to children due to financial insufficiency.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%